No education, no good jobs? Evidence from the relationship between education and labor market segmentation - Carmen Pagés; Marco Stampini (Inter-American Development Bank, Research Department, 2007)
This paper assesses labor market segmentation across formal and informal salaried jobs and self-employment in three Latin American and three transition countries. It looks separately at the markets for skilled and unskilled labor, inquiring if segmentation is an exclusive feature of the latter. Longitudinal data are used to assess wage differentials and mobility patterns across jobs. To study mobility, the paper compares observed transitions with a new benchmark measure of mobility under the assumption of no segmentation. It finds evidence of a formal wage premium relative to informal salaried jobs in the three Latin American countries, but not in transition economies. It also finds evidence of extensive mobility across these two types of jobs in all countries, particularly from informal salaried to formal jobs. These patterns are suggestive of a preference for formal over informal salaried jobs in all countries. In contrast, there is little mobility between self-employment and formal salaried jobs, suggesting the existence of barriers to this type of mobility or a strong assortative matching according to workers' individual preferences. Lastly, for both wage differentials and mobility, there is no statistical difference across skill levels, indicating that the markets for skilled and unskilled labor are similarly affected by segmentation.
Keywords: J210; J240; J310; J630; 330; Labor mobility; segmentation; barriers to entry; skills; informal jobs; Latin America; transition economies; Eastern and Central Europe; Arbeitsmarktsegmentierung; Qualifikation; Arbeitsmobilität; Selbstständige; Bildungsniveau; Albanien; Georgien; Ukraine; Argentinien; Mexiko; Venezuela